Efektivitas Warm Water Footbath dan Aromatherapy Terhadap Kualitas Tidur Lansia: Systematic Review - Alifah Ade Nuary; Endang Triyanto (PSIK FKKMK UGM, 2022)
Background: The aging process in the elderly affects the quality of sleep. More than 50 percent of the elderly meet sleep disorders ranging from mild to severe degrees. Various studies have been carried out to improve the quality of sleep in the elderly, but it is not yet known which is the most effective.Objective: To determine the effectiveness of warm water footbath and aromatherapy on the sleep quality of the elderly.Method: This research includes a systematic review. Search articles using the keywords